2019
DOI: 10.3747/co.26.4591
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Inhibitor–Induced Hypomagnesemia: A Survey of Practice Patterns among Canadian Gastrointestinal Medical Oncologists

Abstract: Background The optimal management of hypomagnesemia (hMg) induced by epidermal growth factor receptor inhibitors (egfris) for advanced colorectal cancer is unclear. We surveyed gastrointestinal medical oncologists in Canada to determine practice patterns for the management of egfri-induced hMg.Methods Based on distribution lists from the Eastern Canadian Colorectal Cancer Consensus Conference and the Western Canadian Gastrointestinal Cancer Consensus Conference, medical oncologists were invited to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Severe hypomagnesemia warrants treatment by intravenous and/or oral magnesium supplementation for the duration of CTX therapy, and cases of CTX dose reduction and discontinuation have been documented [33]. No evidence-based guidelines have currently been developed for the management of hypomagnesaemia in the context of CTX cancer therapy [33]. We demonstrate that CTX inhibits the TRPM6-mediated transcellular Mg transport.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Severe hypomagnesemia warrants treatment by intravenous and/or oral magnesium supplementation for the duration of CTX therapy, and cases of CTX dose reduction and discontinuation have been documented [33]. No evidence-based guidelines have currently been developed for the management of hypomagnesaemia in the context of CTX cancer therapy [33]. We demonstrate that CTX inhibits the TRPM6-mediated transcellular Mg transport.…”
Section: Discussionmentioning
confidence: 87%
“…The symptoms of hypomagnesemia range from depression and muscle spasms to arrhythmias and seizures, and significantly worsen the quality of life of patients [16]. Severe hypomagnesemia warrants treatment by intravenous and/or oral magnesium supplementation for the duration of CTX therapy, and cases of CTX dose reduction and discontinuation have been documented [33]. No evidence-based guidelines have currently been developed for the management of hypomagnesaemia in the context of CTX cancer therapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of Canadian medical oncologists found that most physicians (>90%) regularly monitor MG prior to each EGFRI infusion, and most employ a reactive MG replacement strategy (as opposed to prophylactic). 43 Forty percent of respondents (N=40) favoured IV supplementation alone, while 45% used both oral and IV, and 70% introduced supplementation at Grade 1 hMG and the remainder at Grade 2. Importantly, 30% of oncologists were withholding EGFRIs at Grade 3 hMG and 45% at Grade 4.…”
Section: Management Of Epidermal Growth Factor Receptor-induced Hypomagnesaemiamentioning
confidence: 99%
“…Given this uncertainty, it is not surprising that a survey of oncologists showed that a variety of replacement strategies are used in practice. The majority of respondents used a combination of oral and IV supplements depending on the grade of hMg, with magnesium oxide (MgOx), magnesium rougier, and MgCit being the most commonly used oral agents 11 …”
Section: Introductionmentioning
confidence: 99%